Millennial generation and family literacy within the dissemination of hoax in Whatsapp group - Ririn Puspita Tutiasri; Ade Kusuma (Universitas Negeri Yogyakarta, 2020)
The millennial generation emerges in the era of advanced technology. The characters of the generation tend to have advanced knowledge of both technology and information. This convenience, spreading information easily, causes difficulty identifying whether or not the news is factual. Media literacy is necessary for millennials considering this generation is familiar with modern technology. Data are collected through observations and in-depth interviews. The analysis results that spreading Hoax via group chat is capable of anyone, including close and trusted family members. To prevent the act of disseminating Hoax in family and sibling, thus, a family member has an important role in reminding each other of the relevance of media literacy. This study concludes that knowledge and mastery of technology and the management of information from millennials are essential. Therefore the spreading Hoax is diminished. Literacy from generation to response disseminating Hoax in WhatsApp group provides knowledge to group members, especially parent, to be not gullible and easily provoked to single information. The opportunity of disseminating Hoax through a family group in WhatsApp is higher because of the mutual trust among family members and shared the information without clarifying it.